The Prevalence of Multiple Antibiotic Resistance in Campylobacter spp. From Retail Poultry Meat - Marija Kurinčič; Ingrid Berce; Tina Zorman; Sonja Smole Možina (Food Technology and Biotechnology, 2005)
Macrolides and fluoroquinolones are regarded as drugs of choice for the treatment of human Campylobacter infections. The use of antimicrobials for this purpose as well as in food animal production has resulted in the resistance of Campylobacter spp. to selected antibiotics. Since poultry is one of the most important sources of human Campylobacter infections the use of antibiotics in animal production can shorten the effective therapeutic life of antibiotics for human use. During 2001–2003, over 220 strains of C. jejuni and C. coli were isolated from 60 poultry meat samples from the retail market in Slovenia and further characterized by phenotypic and molecular methods. In this study, 55 sample-representative strains were tested for susceptibility to eight different antibiotics (ampicillin, amoxycillin/ clavulanic acid, ciprofloxacin, erythromycin, gentamicin, nalidixic acid, pefloxacin and tetracycline). Phenotypic procedures (disc diffusion test, E-test) as well as molecular detection of mutations (mismatch amplification mutation assay (MAMA) polymerase chain reaction (PCR)) in case of ciprofloxacin resistance were used. When assuming the results about antibiotic resistance, only 38.2 % of strains tested were susceptible to all antibiotics tested. Regarding ciprofloxacin, 58.2 % of tested strains were found to be resistant (minimal inhibitory concentration, MIC>4 mg/mL). The occurrence of resistance was much higher in C. coli (75.9 %) than in C. jejuni (38.5 %) isolates. The resistance rates to pefloxacin, nalidixic acid, erythromycin and tetracycline were 58.2, 49.1, 14.5 and 12.7 %, respectively. Eleven percent of strains were resistant to erythromycin and ciprofloxacin and 12.7 % of strains were resistant to tetracycline and quinolones. The results show the need for monitoring the prevalence and antibiotic resistance of zoonotic bacteria such as Campylobacter as well as the multiresistance phenomenon of Campylobacter isolates from food in our country.